Effectiveness of the implementation of public services based on the Online Single Submission Risk Based Approach (OSS-RBA) through the One-Stop Integrated Service (PTSP) in Gianyar Regency - I Wayan Suartana (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This study aims to analyze the effectiveness of the Online Single Submission – Risk-Based Approach (OSS-RBA) policy implementation through the One-Stop Integrated Service (PTSP) in Gianyar Regency. The background of the study is based on the gap between the normative objectives of Bali Governor Regulation Number 46 of 2022, which emphasizes acceleration, transparency, and accountability of services, and the actual conditions on the ground, which still face technical, structural, and cultural obstacles. The research method used is descriptive qualitative, with data collection techniques through in-depth interviews, observation, and documentation studies. Data analysis was conducted using the Miles and Huberman interactive model through the stages of data reduction, data presentation, and conclusion drawing. The results show that the implementation of OSS-RBA has encouraged the digitalization of public services, but its effectiveness remains limited. Data from the Gianyar DPMPTSP for the 2021–2025 period shows fluctuations in the number of permit applications and the persistence of backlogs, indicating delays in administrative completion.. The main obstacles identified include low digital literacy among the public, limited capacity of civil servants, weak internet infrastructure in rural areas, and suboptimal policy dissemination. While some medium- and large-scale businesses benefit from the efficiency of the OSS-RBA, MSMEs and the general public face technical difficulties that lower public satisfaction. Overall, the implementation of the OSS-RBA in Gianyar Regency is still considered ineffective. To achieve fast, transparent, accountable, and inclusive public services, strengthening civil servant capacity, equitable distribution of digital infrastructure, and a more participatory policy communication strategy are needed. With these steps, the OSS-RBA has the potential to become a strategic instrument in improving the quality of public services in the region.